Experimental study on novel composite phase change materials with room-temperature flexibility and high-temperature shape stability in a battery thermal management system. (1st June 2023) - Yang, Xiaoping; Deng, Guolan; Cai, Zhuodi; Li, Huaping; Zeng, Jiahao; Yang, Haolin
Highlights: New material with room-temperature flexibility and high-temperature shape stability. The contact thermal resistance of TPS is reduced by 50% compared with that of EPDM. The maximum temperature is controlled below 56 °C at the discharge rate of 2.5C. The temperature difference of the CPCM cooling battery module is lower than 4.0 °C. Abstract: Phase change materials have potential uses in battery thermal management because of their controllable phase change temperature and high latent heat. However, the application of phase change materials is limited by their strong rigidity, difficult assembly, high contact thermal resistance, low thermal conductivity, and leakage. In this study, a novel flexible composite phase change material (CPCM) with good mechanical properties is prepared, which can maintain flexibility at room temperature and shape stability at high temperatures. A thermoplastic styrene-based polymer (TPS) is used as the support material, paraffin is used as the phase change material, and expanded graphite is used as the reinforced thermal conductive filler. Results show that the composites have good flexibility and extensibility at room temperature and can maintain good shape stability at 60 °C and certain pressure. The contact thermal resistance of CPCM is 50% of the contact thermal resistance of similar materials. Thermal management experiments of single battery and square battery modules are designed. After six cycles of 2.5C high-rate discharge, the maximum temperature of the battery module cooled by CPCM is 2 °C and 10.4 °C lower than that of forced air cooling and natural air cooling, respectively. The temperature difference of the battery module is lower than 4.0 °C. This study shows that the new flexible CPCM thermal management system is easy to assemble and can reduce the temperature of battery modules, and this feature is conducive to the application of CPCM.